Explorasi Sayangi Malaysia / E. Tavasuria Elangovan - Elangovan, E. Tavasuria (Corporate Communication Unit, Universiti Teknologi MARA, Perak Branch, 2019)
In conjunction with the month of independence and cel-ebration of Hari Malaysia, a programme called 'EXPLORASI SAYANGI MALAYSIAKU' was organized by the Applied Sciences Tapah Association (Aset) and Faculty of Applied Sciences (FSG), UiTM Perak Branch, Tapah Campus with the aim to inculcate love, affection and spirit among UiTM stu-dents towards the country.